Interactions between the human milk oligosaccharide 2′-fucosyllactose and Bifidobacterium longum subspecies infantis in influencing systemic immune development and function in piglets - Daniels, Victoria C.; Monaco, Marcia H.; Hirvonen, Johanna; Ouwehand, Arthur C.; Jensen, Henrik Max; Mukerjea, Ratna; Christensen, Niels; Lehtinen, Markus J.; Dilger, Ryan N.; Donovan, Sharon M. (Frontiers in Nutrition, 2024)
The oligosaccharide, 2′-fucosyllactose (2′-FL), is a predominant component of human milk. It is a prebiotic for the gut microbiota and influences infant immune development. Bifidobacterium longum subspecies infantis (B. infantis) is a commensal bacterium in the breastfed infant. 2′-FL and a specific strain of B. infantis, Bi-26TM, are commercially available. Herein, the potential synbiotic relationship of 2′-FL and Bi-26TM on immune development was tested. Two-day-old piglets (n = 53) were randomized in a 2 x 2 design to be fed a commercial milk replacer ad libitum without (CON) or with 1.0 g/L 2′-FL (FL). Piglets in each diet were further randomized to receive either glycerol stock alone or Bi-26TM (109 CFU) (BI and FLBI) orally once daily. On postnatal day (PND) 34/35, animals were euthanized and blood was taken for serum cytokine analysis. Additionally, peripheral blood mononuclear cells (PBMC) were isolated for ex vivo stimulation and flow cytometry analysis. Serum and ex vivo cytokines were analyzed by a multivariate model. All other outcomes were analyzed by a 2-way ANOVA with prebiotic and probiotic fixed effects. The significance level was set at P < 0.05, and trends were reported at 0.05 < P < 0.1. Immune cell populations in PBMC were unaffected by the experimental treatment. However, serum interleukin (IL)-1, IL-1RA, IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-18 were all higher (P < 0.05) in FL compared to CON. In isolated PBMC, LPS stimulation resulted in higher IL-1RA and and a trend for higher IFN-γ secretion in FL versus CON. In summary, our findings suggest that 2′-FL stimulates a balanced cytokine profile in healthy piglets, without changing immune cell populations. However, when immune cells are stimulated ex vivo with LPS, 2′-FL primes T-cells for a proinflammatory response, which is moderated by co-administration of Bi-26TM.